Bond behavior of sand-coated deformed glass fiber reinforced polymer rebars. (May 2014) - Xue, Weichen; Zheng, Qiaowen; Yang, Yu; Fang, Zhiqing
Bond behavior of sand-coated deformed glass fiber reinforced polymer rebars was experimentally investigated in this study. A total of 84 specimens, including 30 beam specimens, 48 Losberg pullout specimens, and six RILEM/CEB/FIP pullout specimens, were constructed and tested under monotonic loading. Two failure modes including pullout failure and splitting failure were observed. The pullout failure occurred when the embedment length of specimens was less than 5 times glass fiber reinforced polymer rebar diameter, while the splitting failure occurred when embedment length was more than 5 times rebar diameter. The specimens with the embedment length of 5 times bar diameter failed either by glass fiber reinforced polymer rebars pulling out or by concrete splitting. The results also showed that bond strength of sand-coated deformed glass fiber reinforced polymer rebars was, on average, 59–127% that of the deformed steel rebars. With higher concrete strength, higher bond strength of sand-coated deformed glass fiber reinforced polymer rebars was obtained. When rebar diameter or embedment length increased, bond strength of sand-coated deformed glass fiber reinforced polymer rebars decreased. Based on these results, formulas for the bond strength and the development length of glass fiber reinforced polymer rebars were proposed, considering the effects of concrete strength, bar diameter, embedment length, and rebar outer surface.